The Quality of Gatra Rahayu Men's Clothing in the Theme of Neo Eco Kretek Kudus - Ardhia Regita Cahya Mustika; Sri Endah Wahyuningsih (Universitas Negeri Semarang, 2026)
Systematic studies of the quality of contemporary men's fashion are still limited, especially those that place a single piece of fashion as a single object based on the concept of Neo Eco and local culture, while the fashion industry demands aesthetic, functional, and sustainable work. This study aims to describe the quality of Gatra Rahayu men's clothing in the theme Neo Eco Kretek Kudus as a representation of contemporary aesthetics based on local culture. The quantitative descriptive approach was used with Gatra Rahayu as the object of research as well as expert panelists and trained panelists as subjects. Fashion quality assessment is carried out using instruments that are compiled based on five main aspects, namely design, aesthetics, sewing and finishing techniques, performance or overall appearance, and uniqueness. The data was analyzed using a descriptive percentage technique. The results of the study show that the quality of Gatra Rahayu Fashion is in the very decent category with an overall percentage of 93%, with the uniqueness indicator as the highest aspect of 96% supported by woven details as a visual identity. These findings show that Gatra Rahayu fashion has excellent quality as a unique sustainable fashion product. Academically, this research enriches the study of evaluation of the quality of men's clothing based on a single work, while practically having implications as a reference for the creation of quality and sustainable men's clothing.